Três aspectos fundamentais da Bolha Local - Wilson Reis Junior (2011)
The Sun is located in a low density region and quite irregular shape named Local Bubble (LB). The LB is thought to have been formed by supernovae explosions near the current position of the Sun. These explosions would have swept the interstellar medium, creatinga cavity lled with hot gas. The boundary of the LB is mostly dened by a wall of neutral, cold and dense Hydrogen. Among its fundamental characteristics are i) its origin and age; ii) its boundary with neighbouring bubbles; iii) the physical state of the gas in its interior, including the ionization state; iv) the chemical composition of the material; v) its inner pressure. This work attempts to provide arguments that help answering three of these fundamental aspects of the LB. Limits: by determining the LB boundaries in the direction of the Loop I Superbubble and Orion-Eridanus Superbubble (OE-S). Origin: by mapping the colour excess distribution in the solar neighborhood to test the most recent 3D model of the joint evolution of the LB and Loop I. Chemical composition: by determining the metalicity of the subgroups that form the Scorpio-Centaurus association (Sco-Cen). In our work we have used Strömgrem photometry to build maps of the interstellar reddening and to determine the metalicity of Sco-Cen. The photometric uvbyH datawere obtained from the General Catalogue of Photometric Data, complemented with data from newer catalogs, resulting in a nal sample of 8492 stars. With the photometric results, we have built a detailed map of the color excess distribution in the Sun's vicinity and compared it to the map of the LB boundaries in interstellar neutral Sodiun (NaI).We also corroborate the most recent joint model of the origin and evolution of the LB and Loop I, developed by Avillez & Breitschwerdt (2012). The polarimetry was used to determine the distance of the clouds located in the direction towards OE-S and, through the degree and orientation of the polarization vectors, to make an analysis of the interface's structure. The polarimetric data were collected with theIAG 0,60m and P&E 1,60 m telescopes in Observatório Pico dos Dias (OPD/LNA/MCT) and with the 0,90 m telescope in Cerro Tololo Inter-American Observatory (CTIO - Chile). Our nal sample is composed by 501 stars. About the interface between the LB and Loop I our main results are that: up to 60 - 80 pc the colour excess remains below E(by) 0:m040 in all directions, with 0:m020 being a typical value. The expected transition to E(by) 0:m0700:m100, corresponding to thering's column density, occurs on the western part of the ring at d = 11020 pc, whereas on the eastern side it is not clearly seen before d = 28050 pc. The colour excess distribution does not show the interaction ring, as proposed by Egger & Aschenbach (1995). About the mapping of the colour excess in the solar neighborhood, and the validation ofthe model of the origin and evolution of the LB, the main results can be summed up as follows: the distance to the wall of dust varies with the Galactic longitude and latitude, being the smallest distance about 80 pc for l = 0 at 20 b 40 and for 15 l 30 around the Galactic plane. There are many tunnels and holes in the cavity wall thatconnect the LB with the neighboring bubbles. The colour excess map corroborate the model of origin and evolution of the LB and Loop I, developed by Avillez & Breitschwerdt (2012). About the interface between the LB and the OE-S the analysis of the photometric, polarimetric and NaI data shows that the distance to the interface varies from 150 to 180pc. The distances to the interstellar clouds in this direction are: Loop A d 120 140 pc; G191-52 d 160 pc; G207-50 d 170 pc; Loop B d 170 pc; L1642 d 160 pc; G191-28 d 150 pc; L1569 d 140 pc. The clouds that compose this interface seem to form a ring around the region, this result corroborate the model suggested by Burrows et al. (1993)Although the metallicity of UCL and LCC subgroups are very similar, the LCC one is slightly higher, suggesting that its formation occured after UCL. The metallicity in the US subgroup is greater than the other two subgroups; the metallicity of subgroup UCL is [Fe/H] = -0,032, of LCC is [Fe/H] = -0,012, and of US is [Fe/H] = 0,104. Both results suggest that the interestellar cloud, that generates the US subgroup, was enriched bysupernovae explosions at UCL subgroup.